Protein contain in Cyprinus carpio (Ham.) of experimental and control fishes due to administration of ovaprim, ovatide and pituitary gland extract at Fish Seed Production Centre, Paithan, Aurangabad, Maharashtra State, India - Pawar, M. B.; Quadri, S. A.; Tingote, R. S. (Recent Research in Science and Technology, 2021)
Protein contain is a cornerstone mechanism and form part and parcel of nutritive value in particular rely on season, food intake, breeding and spawning capacity. The protein contain in the fish body constitute as a firsthand source of energy for physiological functions incorporating reproduction. Present investigation display that variations in the protein is observed from the mature fishes of Indian major carps such as Cyprinus carpio comprises 20 to 50cm selected for the estimation of protein study considered as experimental and control fishes upon administration of PGE, ovaprim and ovatide synthetic hormonal doses to the male and female sex ratio separately. Protein in the liver of female major carps may be because of vitellogenin, a lipoprotein which is synthesized in the liver and is transported to the ovary (Wallace, 1985). Moreover, gonadal protein enhanced with maturation amongst these fishes. Protein estimation represents the variations throughout the study period amongst the muscle, gonad and liver. After hormonal injections are given then fishes are kept in the breeding pool at the Fish Seed Production Centres (FSPC) located near Paithan barrage. The protein is estimated upon satisfactory administration of hormonal doses Pituitary Gland Extract and by other two synthetic hormonal doses viz. Ovaprim and Ovatide. Study is conducted during 2013 to 2014.